The iso-Nazarov reaction - Riveira, Martín Jorge (2017)
The construction of five-membered rings is essential in organic chemistry. In this context, pentannulation reactions that provide a straightforward access to cyclopentenones are of particular interest, as these structures are not only embedded in important molecules such as some prostaglandins, but also serve as versatile building blocks in organic synthesis. This review documents the acid-promoted cycloisomerization of conjugated dienals and linearly-conjugated dienones for the construction of cyclopentenones, a transformation that has been largely eclipsed by the well-known Nazarov reaction, i.e. the acid-promoted cycloisomerization of cross-conjugated ketones.